Employing CEFR Speaking Rubrics to Paul-Elder Critical Thinking Framework to Assess Undergraduate Level Students Speaking Skills - Raju, M.; Sivapurapu, Lavanya; B., Mrunalini Sasanka; Thumma, Thirupathi (Journal of Engineering Education Transformations, 2025)
The primary objective of the current research is to improve the speaking skills of undergraduate students by employing the Paul-Elder Critical Thinking Framework (PECTF). Initially, a pre-test was conducted on 61 undergraduate students, following a random speaking test administered to 116 students at a traditional undergraduate college offering conventional courses such as B.A., B.Com., and B.Sc. The pre-test scores were evaluated using the Common European Framework of Reference for Languages (CEFR) speaking descriptors. Students scoring at the A1 level or below were selected for participation in a 6-month Intervention Programme (IP) centered around PECTF. Subsequently, a post-test was conducted, and the recordings were analyzed using the adopted CEFR speaking rubrics. The study revealed significant improvements in speaking skills when comparing the meticulously analyzed results of both pre and post-tests. A qualitative analysis method was extensively utilized in this research. The findings suggest that PECTF can effectively enhance speaking skills, positioning it as a valuable teaching tool for language development, particularly in the context of speaking skills. The researcher sought to explore innovative paradigms and approaches to enhancing speaking skills through the utilization of PECTF.